2012
DOI: 10.1080/03079457.2012.734915
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and genotypic antimicrobial resistance analysis ofCampylobacter jejuniandCampylobacter coliisolated from broiler flocks in northern Italy

Abstract: Genetic variability and genotypic antimicrobial resistance (AMR) of Campylobacter jejuni and Campylobacter coli from commercial broiler farms were investigated in this study. Campylobacter isolates were genetically characterized by random amplified polymorphic DNA (RAPD)-polymerase chain reaction (PCR) and flaA-SVR and flaB-SVR sequence-based typing. Eight RAPD types were identified in C. jejuni and three in C. coli, while 16 fla profiles were detected among all isolates. Further, 13 flaA-SVR and 13 flaB-SVR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
4
15
1
2
Order By: Relevance
“…The existence of high genotypic similarity amongst some strains isolated in Brazil is in contrast with previous studies conducted in several countries that showed high genomic diversity amongst C. coli strains (Harrington et al, 1997;Magnú sson et al, 2011;Giacomelli et al, 2012;Zhang et al, 2014). …”
Section: Discussioncontrasting
confidence: 52%
“…The existence of high genotypic similarity amongst some strains isolated in Brazil is in contrast with previous studies conducted in several countries that showed high genomic diversity amongst C. coli strains (Harrington et al, 1997;Magnú sson et al, 2011;Giacomelli et al, 2012;Zhang et al, 2014). …”
Section: Discussioncontrasting
confidence: 52%
“…Each strain was isolated from different birds commercially reared in four broiler and three turkey farms throughout Northern Italy between 2009 and 2010. 20,21 Antimicrobial susceptibility determination Susceptibility testing was carried out by the disk diffusion method using Mueller-Hinton agar (OXOID, Basingstoke, United Kingdom) supplemented with 5% defibrinated sheep blood (OXOID). Isolates were tested for their susceptibility to 20 antimicrobial drugs belonging to nine classes: aminoglycosides ( Inocula were prepared from overnight growth on tryptic soy agar (OXOID) supplemented with 5% defibrinated sheep blood (OXOID) by suspension in sterile saline (0.9% w/v of NaCl), to obtain a turbidity equivalent to that of a 0.5 McFarland standard.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…One of these methods, flaA gene based PCR-RFLP is one of the widely used method for discrimination of C. jejuni and C. coli isolates [16] . Sequence analysis of short variable regions (SVRs) of flaA and flaB genes is another widely used method for genotyping of Campylobacter isolates, particularly in short-term and localized epidemiological studies [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%